2007
DOI: 10.1177/0269881106072343
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic and pharmacokinetic effects of TPA023, a GABAA α2,3 subtype-selective agonist, compared to lorazepam and placebo in healthy volunteers

Abstract: TPA023, a GABA(A) alpha2,3 alphasubtype-selective partial agonist, is expected to have comparable anxiolytic efficacy as benzodiazepines with reduced sedating effects. The compound lacks efficacy at the alpha1 subtype, which is believed to mediate these effects. This study investigated the effects of 0.5 and 1.5 mg TPA023 and compared them with placebo and lorazepam 2 mg (therapeutic anxiolytic dose). Twelve healthy male volunteers participated in this placebo-controlled, double-blind, double-dummy, four-way, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 48 publications
11
128
2
Order By: Relevance
“…These data are consistent with the lack of efficacy of TPA023 at ␣1-containing receptors, the subtype of GABA A receptor responsible for the sedative effects of diazepam (Rudolph et al, 1999;McKernan et al, 2000) and are in agreement with the pharmacodynamic effects of TPA023, which showed that doses of 0.5 and 1.5 mg did not produce the sedation-like effects (e.g., increased body sway, decreased alertness measured using a visual analog scale) observed with lorazepam (de Haas et al, 2007). Similarly, data with the ␣2/␣3-selective compound TPA023B, which is an imidazotriazine follow-up compound to TPA023, showed that levels of occupancy in the region of 50% could be achieved in the absence of overt sedation (Van Laere et al, 2008;Atack et al, 2009b).…”
Section: Occupancy Of Benzodiazepine Binding Sites By Tpa023 21supporting
confidence: 87%
See 3 more Smart Citations
“…These data are consistent with the lack of efficacy of TPA023 at ␣1-containing receptors, the subtype of GABA A receptor responsible for the sedative effects of diazepam (Rudolph et al, 1999;McKernan et al, 2000) and are in agreement with the pharmacodynamic effects of TPA023, which showed that doses of 0.5 and 1.5 mg did not produce the sedation-like effects (e.g., increased body sway, decreased alertness measured using a visual analog scale) observed with lorazepam (de Haas et al, 2007). Similarly, data with the ␣2/␣3-selective compound TPA023B, which is an imidazotriazine follow-up compound to TPA023, showed that levels of occupancy in the region of 50% could be achieved in the absence of overt sedation (Van Laere et al, 2008;Atack et al, 2009b).…”
Section: Occupancy Of Benzodiazepine Binding Sites By Tpa023 21supporting
confidence: 87%
“…Hence, the affinity of TPA023 for the different subtypes of GABA A receptors ranges from 0.2 to 0.4 nM, whereas SL65.1498 has affinity at the ␣1, ␣2, and ␣3 subtypes, ranging from 17 to 80 nM, with even lower affinity (215 nM) at the ␣5 subtype (Griebel et al, 2001). The C max values for the 0.5-and 1.5-mg doses of TPA023 were 5 and 13 ng/ml, respectively (de Haas et al, 2007), whereas respective values for the 2.5-, 7.5-, and 25-mg doses of SL65.1498 were 37, 126, and 375 ng/ml, respectively (de Haas et al, 2009). Accordingly, the plasma drug concentrations required for effects on saccadic eye movement peak velocity for TPA023 and SL-65.1498 were 5 and 375 ng/ml, respectively, again emphasizing the relative potency of TPA023.…”
Section: Occupancy Of Benzodiazepine Binding Sites By Tpa023 21mentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, TPA-023 showed anticonvulsant activity in a mouse pentylenetetrazole seizure model [370]. TPA-023 had significant dose dependent effects on saccadic peak velocity that approximated the effects of lorazepam [371]. However in contrast to lorazepam, TPA-023 had no detectable effects on saccadic latency or inaccu-racy.…”
Section: Tpa-023mentioning
confidence: 99%